Clinical and surgical outcomes of robot-assisted versus conventional total hip arthroplasty: a systematic overview of meta-analyses. Issue 12 (December 2021) - Kort, Nanne; Stirling, Patrick; Pilot, Peter; Müller, Jacobus Hendrik
Abstract : Robot-assisted total hip arthroplasty (THA), in comparison to conventional THA, improves radiographic outcomes, but it remains unclear whether it alters complication rates, clinical and functional outcomes, and implant survival. The purpose of this systematic overview was to summarize the findings of the most recent meta-analyses that compare clinical and surgical outcomes of robot-assisted versus conventional THA. Two readers independently conducted an electronic literature search, screening and data extraction from five electronic databases. Inclusion criteria were: meta-analyses evaluating robot-assisted versus conventional THA in terms of radiographic outcomes, clinical and functional scores, and complications and revision rates. The literature search returned 67 records, of which 14 were duplicates and 49 were excluded, leaving three meta-analyses published within the past two years for data extraction and analysis. The present overview of meta-analyses suggests that, compared to conventional THA ( n = 3011), robot-assisted THA ( n = 1813) improves component placement and reduces intraoperative complications. The overview also affirms that robot-assisted THA could extend surgery by 20 minutes, and increases risks of postoperative heterotopic ossification, dislocation, and revision. None of the meta-analyses found significant differences in clinical or functional scores between robot-assisted and conventional THA. Future studies and reviews should make a clear distinction between active and semi-active robotic assistance, address technology matureness, and describe the experience of surgeons with robotic assistance. Cite this article: EFORT Open Rev 2021;6:1157-1165. DOI: 10.1302/2058-5241.6.200121